(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The article examines the sentence no. 10/2024 by the Constitutional Court, which declared the illegitimacy of Article 18 of the Prison Regulations concerning the limitation of private visits for detained persons without direct visual supervision by custodial personal. The Court affirmed that, in the absence of security reasons, detainees have a right to their affectivity and intimacy, ensuring their dignity. The contribution also analyzes the Spanish penitentiary system, highlighting the conflict between protecting fundamental rights and the ordinamental needs for order and security, with the prisoner as the figurative “place” of a clash between the individual and the punitive power.